« No guys with attitude ». Sociabilité et hiérarchie sexuelle dans une sex party gaie de New York - Etienne Meunier (Genre, Sexualité et Société)
Over the past 30 years in NYC, most gay bathhouses and sex clubs were forced to shut down, moving group sex practices to private events. Past research has observed that group sex venues were democratic places where men of different age, body, and social group came together for convivial sexual and social interaction. Queer theorists have expressed a concern that the “privatization” of group sex would lead to more division and exclusion in gay sexual cultures. This article observes these issues by presenting original ethnographic data collected in one gay private sex party in NYC. Participants clearly felt that some parties were hierarchized, especially because of the “guy with attitude,” a young and attractive, but denigrating young man. Participants tried to keep these guys at bay and preferred events where men were less selective and participated more in the group sexual activity. The dynamics of inclusion and exclusion of sex parties lead men to adapt their sexual desires and practices to match the values of the places where they feel they can belong.